Neuritis des N. vestibularis inferior: Diagnose mittels VEMP-Diagnostik - Walther, Leif Erik; Repik, Ines (HNO, 2012)
Vestibular evoked myogenic potentials (VEMP) are a new method to establish the functional status of the otolith organs. The sacculocollic reflex of the cervical VEMP to air conduction (AC) reflects predominantly saccular function due to saccular afferents to the inferior vestibular nerve. We describe a case of inferior vestibular neuritis as a rare differential diagnosis of vestibular neuritis. Clinical signs were a normal caloric response, unilaterally absent AC cVEMPs and bilaterally preserved ocular VEMPs (AC oVEMPs).